2018
DOI: 10.1016/j.eats.2017.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Primary Anterior Cruciate Ligament Repair With Augmentation

Abstract: Anterior cruciate ligament (ACL) tears are usually managed by reconstruction with autograft or allograft, but primary repair in carefully selected patients is a reasonable option. Proximal avulsions presenting early with excellent tissue quality are amenable to repair and healing. Restoration of native ACL preserves its proprioceptive and kinematic functions. A repair is less invasive and avoids graft-related problems, and faster rehabilitation is possible. Protection for the repair in the early stages will al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Most other ACLR papers employing FiberTape® augmentation are technical notes without patient outcomes [8,12,26]. A prospective 2-year study published by Heusdens et al [27] reported improved post-operative outcomes of suture augmentation in the context of ACL repair, with a 4.8% rerupture rate over the period, but other published papers using FiberTape® augmentation for ACL repair are also limited to technical notes [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most other ACLR papers employing FiberTape® augmentation are technical notes without patient outcomes [8,12,26]. A prospective 2-year study published by Heusdens et al [27] reported improved post-operative outcomes of suture augmentation in the context of ACL repair, with a 4.8% rerupture rate over the period, but other published papers using FiberTape® augmentation for ACL repair are also limited to technical notes [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…A more recently employed device to augment an ACLR is FiberTape® (Arthrex, Naples, Florida, USA) [8,12,14,26], with a retrospective comparison of outcomes in patients undergoing ACLR with and without suture augmentation with Fiber-Tape® demonstrating improved outcomes with augmentation [14]. However, studies using FiberTape® augmentation are limited and a greater number of published papers exist related to the use of FiberTape® reinforcement in the context of ACL repair [27][28][29], rather than reconstruction, although even then many of these are technical notes and not studies reporting patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of knowledge of the anatomy of the insertion of the hamstring tendons may lead to technical problems during harvesting, such as injury to the saphenous nerve and technical difficulty in harvesting because the incision was made in an inappropriate location. 8,11,12 It is very common for the hamstring tendons to be lost, with a consequent need to harvest another graft from a second donor site. 1,12 There is a shortage of articles in the literature relating to basic applied anatomy specifications of the ST-G tendons focused on correct harvesting.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, potential complications can occur during graft harvest; these include inadvertent division of the tendons; disinsertion of the pes anserinus; damage to the medial collateral ligament (MCL); and neurologic injury, mostly to the infrapatellar branch of the saphenous nerve (IPBSN). 8,9 The rate of MCL injury can increase during the learning curve for ST-G tendon harvesting. The proximity of the hamstring tendons in the pes anserinus area to the IPBSN predisposes the nerve to damage during harvesting.…”
mentioning
confidence: 99%
“… 18 Promising outcomes have also been seen in conjunction with medial knee injuries 19 , 20 and ACL repairs. 21 , 22 Recently, Bachmaier et al. 23 investigated independent suture tape reinforcement of soft tissue grafts for ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%